Battle for “Donat”: а discussion about the old and new classical philology in Russia (1847–1848) - Kira Ilina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the 1830–40s (time of the transformation of classical philology into a scientific discipline) during discussions in the Ministry of Public Education and in the public sphere, norms for teaching classical disciplines were developed and the number of ancient languages textbooks were rapidly increased. The article focuses on the reconstruction of the discussion about the Latin language textbook “Donat”, prepared by Moscow University professor Karl Hofman. The heterogeneity of the disciplinary community of classical philologists and rival systems of values, arguments, and authorities are traced in this discussion. On the one hand, A. M. Kubarev followed traditional pedagogical methods and textbooks of grammatical authorities associated with the history of Russian classical philology of the 18th century and approved by the Ministry of Public Education. On the other hand, K. Hofman and his disciples considered it necessary for a classical philologist to know the current level of development of classical philology, as well as to appeal to modern philologists and to change the methods of teaching Latin. Critical publications in thick literary magazines (“Otechestvennye zapiski”, “Sovremennik”, “Moskvityanin”) and archival materials from the Manuscript Department of the Russian State Library and from the Central State Archive of Moscow were used as historical sources. Public opinions, ways of the discussion, evaluation practices, ethically (un)acceptable statements identify are found in published sources. Unpublished and unknown to ordinary people part of the discussion, as well as the historical contexts of the debate and biography nuances of its participants can be detected in office documents, personal correspondence, a draft of an unpublished article. The research methodology is based on a combination of traditional historical methods and approaches developed in the framework of the history of science, the history of disciplines and the sociology of literature.